Acidulated soybean oil in diets for rainbow trout alevins (Oncorhynchus mykiss) on its performance under commercial conditions - Elguera, M. A.; Vergara, V. J.; Vega-Vilca, J. F. (Peruvian Agricultural Research, 2019)
Objectives: To evaluate the inclusion of acidulated soybean oil in diets for rainbow trout alevins (Oncorhynchus mykiss) on its performance under commercial conditions. Methodology: Forty thousand and five hundred rainbow trout alevins were used and raised in ponds. Three levels of acidulated soybean oil included in the diet of 0.0, 2.5 and 5.0 % were evaluated. The study was conducted for 60 days. The variables evaluated were weight gain, feed intake, feed conversion, length gain, survival, growth rate, protein efficiency retention and feed cost / kg of weight. The data obtained were analyzed using the analysis of variance of a completely randomized design. Results: The levels of acidulated oil used in the diets for trout alevins had a similar effect on the evaluated variables . (P > 0.05). Conclusions: The acidulated soybean oil can partially or totally replace the crude soybean oil, up to 5.0 % in diets for rainbow trout alevins Keywords: Soybean oil, alevins, trout, performance.